Women Political Leaders as Agents of Environmental Change - Berniell, María Inés (2025)
This paper explores how female political leaders impact environmental outcomes and climate change policy actions using data from mixed-gender mayoral races in Brazil. Using a Regression Discontinuity design we find that, compared to male mayors, female mayors significantly reduce greenhouse gas emissions. This effect is driven by a reduction in emissions intensity (CO2e/GDP) in the Land Use sector, without changes in municipal economic activity. Part of the reduction in emissions in the Land Use sector is attributable to a decline in deforestation. We examine potential mechanisms that could explain the positive environmental impact of narrowly electing a female mayor over a male counterpart and find that in Amazon municipalities, female elected mayors allocate more space to the environment in their government proposals and are more likely to invest in environmental initiatives. Differences in the enforcement of environmental regulations do not explain the results.